Analysis Of Factors Influencing The Timeliness Of Financial Reporting On The Indonesia Stock Exchange (IDX) - Adriana, Nana (SEAN Institute, 2024)
The timeliness of financial reporting is an important aspect in maintaining corporate transparency and accountability, especially for companies listed on the Indonesia Stock Exchange (IDX). This study aims to analyze factors that affect the timeliness of financial reporting on the IDX, including internal company variables such as company size, profitability, leverage, and complexity of operations. This study uses a quantitative method with a logistic regression approach to identify the influence of each variable on the likelihood of timely financial reporting. The secondary data used is obtained from the annual financial statements of companies listed on the IDX during a certain period. The results show that company size and profitability have a positive and significant effect on the timeliness of reporting, while leverage and complexity of operations show a diverse influence depending on the characteristics of the industry sector. The study also highlights that external factors such as regulation and compliance with accounting standards can affect the timeliness of reporting. These findings have important implications for company management, investors, and regulators in understanding the factors that encourage or hinder the timeliness of financial reporting. By understanding these factors, companies can improve the quality of financial reporting that is in line with stakeholder expectations and meets the demands of the capital market.